The frequency and clinicopathological significance of NRAS mutations in primary cutaneous nodular melanoma in Indonesia - Rinonce, Hanggoro Tri; Sastri, Deflen Jumatul; Trisnawati, Fita; Kameswari, Bidari; Ferronika, Paranita; Irianiwati, Irianiwati (Wiley Periodicals LLC, 2022)
Background: Melanoma is a lethal skin malignancy with a high risk of metastasis, which prompts a need for research on treatment targets and prognostic factors. Recent studies show that the presence of neuroblastoma RAS viral oncogene homolog (NRAS) mutation can influence cell growth in melanomas. The NRAS mutation, which stimulates the mito- gen-activated protein kinase (MAPK) signaling pathway, is associated with a lower survival rate. However, evidence from Indonesia population is still very rare. Further understanding of the role of NRAS mutations in Indonesian melanoma cases will be crucial in developing new management strategies for melanoma patients with NRAS mutations. Aims: To explore the frequency of NRAS mutations and their clinicopathological associations in patients with primary nodular cutaneous melanoma in Central Java and Yogyakarta, Indonesia. Methods and results: Fifty-one paraffin-embedded tissue samples were collected from primary nodular skin melanoma cases between 2011 and 2019 from the two largest referral hospitals in Yogyakarta and Central Java, Indonesia. The NRAS mutation status was evaluated using qualitative real-time polymerase chain reaction (qRT-PCR). The association of NRAS mutation was analyzed with the following: age, gender, location, lymph node metastasis, ulceration, mitotic index, tumor-infiltrating lymphocytes (TILs), necrosis, tumor thick ness, lymphovascular invasion (LVI), and tumor size. NRAS mutations were detected in 10 (19.6%) samples and predominantly observed (60%) in exon 2 (G12). These mutations were significantly correlated with lymph node metastases (p = .000); however, they were not associated with other variables analyzed in this study. Conclusions: The prevalence of NRAS mutations in primary nodular cutaneous melanoma cases from Indonesia is consistent with previous studies and is significantly associated with increased lymph node metastases. However, the predominant mutation detected in exon 2 (G12) is different from previous studies conducted in other countries. This suggests that melanoma cases in Javanese people have different characteristics from other ethnicities.